Mitophagy regulates mitochondrial number following pharmacological induction of mitochondrial biogenesis in renal proximal tubule cells - Hurtado, Kevin A.; Schnellmann, Rick G. (Frontiers in Pharmacology, 2024)
Background: Mitochondrial biogenesis (MB) induction through the activation of the 5-Hydroxytriptamine (5-HT) 1F receptor (HTR1F) is a promising mechanism for the treatment of diseases characterized by mitochondrial dysfunction, such as acute kidney injury (AKI). While several studies report pharmacological activation of MB in the proximal tubule, it is unclear how the proximal tubule regulates itself once the pharmacological activation is removed. Mitophagy is the process of selective mitochondria degradation. We hypothesize that mitophagy decreases mitochondrial number after pharmacological stimulation and restore mitochondrial homeostasis. Methods: Renal proximal tubules were treated at time 0hr with LY344864 or vehicle for 24 h and then removed. LY344864, a selective HTR1F agonist, induces MB in renal proximal tubules as previously reported (Gibbs et al., Am J Physiol Renal Physiol, 2018, 314(2), F260–F268). Vehicle and pharmacological reagents were added at the 24 h time point. Electron microscopy was used to assess mitochondrial morphology, number, and autolysosomes. Seahorse Bioscience XF-96 extracellular flux analyzer was used to measure maximal mitochondrial oxygen consumption rates (FCCP-OCR), a functional marker of MB. Results: LY344864 treatment increased FCCP-OCR, phosphorylation of protein kinase B (AKT), peroxisome proliferator-activated receptor γ coactivator-1alpha (PGC-1α), and mitochondrial number after 24 h. These endpoints decreased to baseline 24 h after LY344864 removal. Treatment with ROC-325, an autophagy inhibitor, increased Sequestosome-1 (SQSTM1/P62) and microtubule-associated protein-1 light chain 3 (LC3B) after 24 h of treatment. Also, ROC-325 treatment sustained the elevated mitochondrial number after LY344864 pre-treatment and removal. Conclusion: These data revealed that inhibition of autophagy extends elevated mitochondrial number and function by preventing the lysosomal degradation of mitochondria after the removal of LY344864.